Pengaruh Disiplin Kerja terhadap Produktivitas Kerja Karyawan di PT Viduo Vi Prabumulih - Sa Harahap, Reza Oktafian; Isni Adriana; Dameria Siregar, Lina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine how the influence of work discipline on employee work productivity at PT Viduo VI Prabumulih. The population in this study amounted to 80 people with the sampling method using the saturated sample method. The data used in this study used primary data with data collection techniques through questionnaires. The data analysis technique used is simple linear regression analysis. The results of this study indicate that work discipline has a positive and significant influence on employee work productivity at PT Viduo VI Prabumulih.